Assessment of rational use of drugs using World Health Organisation’s indicators in a government hospital of central Nepal - Deo, Satish; Dahal, Aashma; Sapkota, Biswash (Journal of Kathmandu Medical College, 2023)
Background: Irrational practice of medicines use is a serious problem of health care setting. Objectives: The primary aim of this study was to assess rational use of drug (RUD) at a government hospital of central Nepal using World Health Organisation (WHO) core drug use indicators. Methods: This descriptive, cross-sectional study was conducted from 2022 November to December at Hetauda Hospital after ethical clearance. A total of 500 prescriptions were taken retrospectively by using systematic sampling method for prescribing indicators whereas 100 patient interviews were conducted prospectively to study patient care indicators. For facility-based indicators different departments of the selected hospital were visited to collect the data. Results: The mean values of prescribing indicators of RUD in the surveyed hospital compared with WHO values for prescription of generics, antibiotics, and injections was found to be 6.3% (n = 119) vs.100%; 28.4% (n = 142) vs. 20-26.8%; and 1.2% (n = 6) vs. 13.4-21.1% respectively. Another discrepancy reported was regarding the mean number of drugs per prescription which was found to be more than the WHO optimal value (3.77 vs. 1.6-1.8). The average consultation time and dispensing time was found to be 5.52 ± 4.49 minutes vs. 10 minutes and 111 ± 60.2 seconds vs. more than 180 seconds, respectively as compared with WHO value. Conclusion: According to the WHO/RUD core drug use indicators, rational medicine use is not attained in most prescribing and patient care components. It is recommended that health institutions should co-operate to promote the judicious use of medications.